ANALISIS RESIKO KONSENTRASI DEBU (TSP) DAN TIMBAL (Pb) DI PINGGIR JALAN TERHADAP KESEHATAN MANUSIA STUDI KASUS KOTA YOGYAKARTA - Haryono Setyo Huboyo; Syafrudin Syafrudin (Diponegoro University, 2007)
Motor vehicle emission generate numerous harmful pollutants in the street every day, some of them arecarcinogenic such as TSP and lead. Yogyakarta is one of represent city which has high traffic load so that thecontamination effect is pronounced. This research was aimed at analysing the risk from related pollutant forpeople who live or work in the vicinity of main streets. This work consists of four steps i.e hazardidentifications, exposure assessment, toxicity assessment, and risk characterization. High volume samplerwas used to catch ambient TSP, spektrophotometer was used for Pb analysis further. Fifteen main streets hadbeen selected for field sampling. Hazard identifications to TSP and Pb concentration was mirrored toambient air standard that maximal concentration for the TSP is 230 μg/m3 and for Pb is 2 μg/m3. Onexposure assessment the TSP concentration in Wates street, Janti, Godean street, Solo street, PKUMuhammadiyah, and STTL exceed ambient air standard (Kep. Gub. DIY No. 513/ 2002), whereas for Pb, allstreets comply to standard. Toxicity assessment revealed that TSP intake in all place was safe since thecalculated intake were still under maximal intake 0,074 mg/kg.day. The circumstance was also true for Pbthat the intake do not exceed 0,00065 mg/kg.day. Based on risk characterization result, it can be concludedthat level of total risk in all places was less than unity so it implies that in those area was safe for dailyactivities in specified time with respect to pollutants of interest. However the relative high risk was pointedout to the Ahmad Dahlan street and the lowest risk was in the Magelang street. Average total risk inYogjakarta city was 0,034.